Spin-off, market structure, and deposit funds: case in the Indonesian Islamic banking industry - Mohammad Nur Rianto Al Arif (Universitas Islam Indonesia, 2018)
The regulator had imposed some Islamic business units to do the spin-off after the enactment of the Islamic banking act (The Act No. 21 of 2008). The aim of this research is going to examine the relationship between spin-off, market structure, and deposit funds. Regression with panel data was using as a tools of analysis. The result shows that there is a difference in deposit funds between the spin-off banks and non-spin-off banks. Besides that, the result also indicates that there is a relationship between spin-off, market structure, and deposit funds in the Indonesian Islamic banking industry. The result implies that the regulator should a policy to accelerate the Indonesian Islamic banking industry.